Tingkat Risiko dan Keluhan Musculoskeletal Disorders (MSDs) pada Pengguna Jasa Perahu Wisata Tradisional - Maharsa Pradityatama; I Made Suartika; Hilda Fatihah (Universitas Mercu Buana, 2026)
Tourism represents a key sector contributing to economic growth, employment generation, and poverty reduction. In marine tourism, traditional tourist boats function as primary transportation; however, their seating design is often not ergonomically optimized, potentially leading to musculoskeletal discomfort among users. This study aims to evaluate the prevalence and distribution of musculoskeletal complaints associated with seating on traditional tourist boats using the Nordic Body Map (NBM) instrument. Data were collected from 30 Indonesian respondents aged 17–45 years. The findings reveal that the highest prevalence of discomfort occurred in the buttocks (90%) and lower back (83%), whereas the lowest prevalence was observed in the right ankle (29%) and right calf (30%). The mean discomfort score was 60, which falls within the moderate risk category (range 50–70), indicating the necessity for ergonomic intervention. These findings highlight the importance of redesigning seating facilities on traditional tourist boats to improve user comfort and mitigate the risk of musculoskeletal disorders.